Diabetic foot spa, bueger’s allen exercise and music therapy on foot sensitivity, the ankle brachial index and sleep quality for diabetes mellitus in Indonesia (Bangladesh Journal of Medical Science, 2023)
Background : One of metabolic disease disorders is Diabetes Mellitus (DM) with signs of hyperglycemia due to impaired insulin secretion and/or cellular insulin resistance. Diabetic ulcers are a complication of DM on the skin, beginning with a feeling of numbness and tingling. Symptoms or signs and symptoms of DM cause symptoms that occur because these clinical symptoms are often on a daily basis so that this can interfere with sleep.Objective : analyzed the effect of diabetic foot spa, bueger’s allen exercise and music therapy on foot sensitivity, ankle brachial index and sleep quality.Methods : This study with quasy experiment pre-post control group design. The population in were DM type 2 with sample 150 respondents, who were divided to intervention and control group. Collecting data using the observation sheet for diabetic foot SPA; The tools used were hammer reflex and cotton swabs to assess foot sensitivity, sphygmomanometer to measure abi and PQSI questionnaire. Data were analyzed by wilcoxon and t test.Results : The test results showed that foot sensitivity with p value = 0.000 (p>0.05), ankle brachial index with p-value = 0.001 (p>0.05) and sleep quality with p value = 0.000 (p>0.05).Conclusion : Implementation of diabetic foot spa, bueger’s allen exercises and music therapy are effective to increase foot sensitivity, ankle brachial index and sleep quality in patients with diabetes mellitus type 2.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 536-544